The Readability of Outpatient Plastic Surgery Clinic Letters: Are We Adhering to Plain English Writing Standards? - Thomas Dobbs (Plastic Surgical Nursing, 2021)
The readability of letters sent to patients plays a pivotal role in facilitating joint decision making and positive health outcomes. Guidance suggests that all correspondence should be directed to patients. Covid-19 led to an increase in direct-to-patient communication. This study aims to determine the quantity and quality of plastic surgery clinic letters sent to patients before and during the Covid-19 pandemic. A total of 127 pre-Covid clinic letters from November to December 2019 and 103 peri-Covid clinic letters from April to May 2020 were identified and assessed for readability. Text was analyzed using a standardized set of commonly used readability formulae, including SMOG, Flesch Reading Ease, and the Coleman-Liao Index. A total of 100 pre-Covid and 58 peri-Covid letters were suitable for inclusion. Median results for formulae that output a U.S. grade score ranged between 9 and 12.9 for letters written prior to Covid-19 and 9 and 13.2 for those written during Covid-19. Eight percent of letters were sent to patients pre-Covid, increasing to 28% during the pandemic. Letters sent to patients had a median grade score of between 8 and 12 prior to Covid-19 and 8 and 10.6 during Covid-19. Letters sent to clinicians ranged between 9 and 13 and 9 and 13.3, respectively. Outpatient plastic surgery letters are written at a readability level too high to facilitate understanding among the general population. The increase in direct-to-patient contact during the Covid-19 outbreak has not led to a significant improvement in the readability of clinic letters. The authors suggest an increase in letter standardization and raising awareness of readability when writing clinic letters. [Abstract copyright: Copyright © 2021 International Society of Plastic and Aesthetic Nurses. All rights reserved.]